(untitled) - Zemach, Dorothy E. (Macmillan, 2003)
College writing provides stedents with a variety of group,pair and individual planning and writing tasks,models of writing that are based on real assignments.
Keywords: Report writing,Anh ngữ,Kỹ năng viết báo cáo,English language; Problems, exercises, etc.,Tu từ học,Câu hỏi và bài tập,Rhetoric